PHYSICOCHEMICAL CHARACTERISTICS AND PHARMACOLOGICAL ACTIVITY OF SACHA INCHI SEED OIL (Plukenetia volubilis L.): A LITERATURE REVIEW - Saputri, Ulan Mulyani; Irnawati, Irnawati; Sahidin, Sahidin; Arba, Muhammad; Fristiohady, Adryan (Universitas Muhammadiyah Magelang, 2025)
Sacha inchi (Plukenetia volubilis L.) of the family Euphorbiaceae is native to Peruvian in the Amazon forest. SaIn seeds are known to contain a significant fatty acid such as linolenic acid (Omega-3), linoleic acid (Omega-6), and oleic acid (Omega-9). Several studies have shown the benefits of Sacha inchi (SaIn) for various pharmacological activities based on its compound content. The aim of this review article is to provide information about pharmacological activities and describe the physicochemical characteristics of SaIn seed oil. The method used to make this article review is a literature study gathered from national and international journals published in the last ten years through Google Scholar, NCBI-Pubmed, and Crossref with search keys in the form